Examination Stress During COVID-19 and Its Coping Interventions Used by Medical Students of Pakistan - Sadaf, Sana; Ishtiqa, Sania; Jahan, Musarrat; Farooq, Fareeha; Mushtaque, Saher; Sukhia, Dr (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the examination stress and anxiety score during COVID-19 pandemic and to identify coping mechanisms adapted by medical students.Study Design: Cross-sectional study.Place and Duration of Study: Sir Syed College of Medical Sciences for Girls, Karachi, from Apr-May 2021.Methodology: A total of 250 students were recruited in the study and validated questionnaire was used for data collection. Test anxiety scores were calculated from a previous study scale by Nist and Diehl (1990). Data was analyzed by using SPSS-23.Results: The mean age of students was 20.1 ± 0.6 years. 74 (29.6%) students felt stress sometimes, 40 (16.0%) students felt always and 30 (12.0%) students never felt stressed before examination. Students who reported improved performance during the examination due to stress were 121 (48.4%). 76 (30.4%) students reported decrease in performance and 53 (21.2%) reported that their stress did not affect their performance. Students were inquired regarding the methods to cope the stress. 78 (31.2%) students reported that they took study break, 66 (26.4%) students spent time with family and friends, 49 (19.6%) found solace in sleep, 30 (12.0%) students listened to music, 13 (5.2%) used beverages (tea, coffee), 11 (4.4%) used numerous combinationsof methods, and only 3 (1.2%) students exercised. It was found that 158 (77%) students experienced healthy anxiety, 68 (27.2%) unhealthy anxiety, and 22 (8.8%) students were anxiety-free.Conclusion: Examination stress among medical students has increased during COVID-19 and various coping methods are used by the students to prevent anxiety. College.....